2020
DOI: 10.7759/cureus.8024
|View full text |Cite
|
Sign up to set email alerts
|

Constrictive Pericarditis: A Commonly Missed Cause of Treatable Diastolic Heart Failure

Abstract: Bhattad et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The causes of low cardiac output syndrome are related to the incomplete resection of thickened pericardium, unsatisfactory relief of left ventricular compression, excessive ventricular dilatation after pericardial dissection, myocardial weakness, and heart failure [ 8 ]. In our study, univariate and multivariate analyses showed that postoperative LVEDD ( P < 0.001) is associated with multiorgan failure (Table 5 ), indicating that the incomplete resection of thickened pericardium and unsatisfactory relief of left ventricular compression are associated with multiorgan failure following pericardiectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of low cardiac output syndrome are related to the incomplete resection of thickened pericardium, unsatisfactory relief of left ventricular compression, excessive ventricular dilatation after pericardial dissection, myocardial weakness, and heart failure [ 8 ]. In our study, univariate and multivariate analyses showed that postoperative LVEDD ( P < 0.001) is associated with multiorgan failure (Table 5 ), indicating that the incomplete resection of thickened pericardium and unsatisfactory relief of left ventricular compression are associated with multiorgan failure following pericardiectomy.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kidney Disease Improving Global Outcomes classi cation, if serum creatinine increases by ≥ 0.3 mg/dl (26.5 μmol/l) within 48 hours, serum creatinine is 50% higher than the baseline within rst seven days, or urine output is below 0.5 ml/kg/hour for six hours, the patient is considered to have acute renal injury. [12,13] Multiorgan failure is regarded as a continuous process of varying levels of organ failure rather than an all-or-none event. To characterize multiorgan failure, six different organ systems are regarded as "key organs": lungs, cardiovascular system, kidneys, liver, coagulation system, and central nervous system.…”
Section: Preoperative Diuresis Protocolmentioning
confidence: 99%
“…The causes of low cardiac output syndrome are related to the incomplete resection of thickened pericardium, unsatisfactory relief of left ventricular compression, excessive ventricular dilatation after pericardial dissection, myocardial weakness, and heart failure. [11][12][13] In our study, postoperative LVEDD of group with multiorgan failure was signi cantly smaller (not larger) than that in group without multiorgan failure (40.2±0.4 mm versus 44.0±0.1 mm, P 0.001) and univariate and multivariate analyses showed that postoperative LVEDD (P 0.001) is associated with multiorgan failure (Table 7), indicating that the incomplete resection of thickened pericardium and unsatisfactory relief of left ventricular compression are associated with multiorgan failure following pericardiectomy.…”
Section: Incomplete Pericardial Dissection Is Associated With Multiorgan Failure Following Pericardiectomymentioning
confidence: 99%
“… 2 Furthermore, no test in isolation can provide definitive diagnostic evidence for constrictive pericarditis. 3 Here, we present a case of a patient presenting with acute liver failure, where the diagnosis and management of constrictive pericarditis was guided by multi-modality cardiovascular imaging.…”
Section: Introductionmentioning
confidence: 99%